Case-control study examining the impact of oral health problems on the quality of life of the families of preschoolers - Ramon Targino FIRMINO; Monalisa Cesarino GOMES; Raquel Gonçalves VIEIRA-ANDRADE; Carolina Castro MARTINS; Saul Martins PAIVA; Ana Flávia GRANVILLE-GARCIA
Abstract The aim of this study was to evaluate the impact of dental caries, traumatic dental injuries (TDI), toothaches, and malocclusion on the oral health-related quality of life (OHRQoL) of the families of Brazilian preschool children. A population-based, matched case-control study involving 415 pre-schoolers aged 3-5 years was conducted. The case (impact on OHRQoL) and control groups (no impact on OHRQoL) were matched for age, gender, and family income at an 1:4 ratio. Impact on the OHRQoL of a family was assessed using the Brazilian version of the Early Childhood Oral Health Impact Scale (B-ECOHIS). Dental caries, TDI, and malocclusion were diagnosed by three calibrated dentists (Kappa: 0.85-0.90). Data analysis involved descriptive statistics and conditional logistic regression analysis (p ≤ 0.05; 95%CI). There were no differences between the cases and controls regarding age, gender, and family income (p > 0.05). The most frequent responses on the B-ECOHIS among cases were "felt guilty" (68.6%) and "been upset" (48.2%). The following variables were significantly associated with negative impacts on family OHRQoL (cases): caries severity (OR = 6.680; 95%CI = 2.731-16.349), a history of toothache (OR = 2.666; 95%CI = 1.492-4.765), parental rating of the child's oral health as poor (OR: 1.973; 95%CI = 1.072-3.634), and parent's/caregiver's age (OR = 2.936; 95%CI = 1.077-3.478). Anterior open bite was positively associated with OHRQoL (OR = 4.050; 95%CI = 1.333-12.314). Caries severity, a history of toothache, parental rating of the child's oral health as poor, and younger parents/caregivers were associated with impact on the OHRQoL of the families of preschoolers.